2005
DOI: 10.1111/j.1365-2036.2005.02568.x
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors reduce the bioavailability of dietary vitamin C

Abstract: SUMMARYBackground: The gastric juice concentration of vitamin C is reduced in subjects with elevated intragastric pH. This is probably because of the fact that the vitamin is unstable at non-acidic pH and undergoes irreversible denaturation. Aim: To determine whether elevation of intragastric pH reduces the bioavailability of dietary vitamin C. Methods: Plasma vitamin C was measured before and after a course of omeprazole 40 mg/day for 4 weeks in 14 Helicobacter pylori positive and 15 H. pylori negative subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 22 publications
0
32
0
2
Order By: Relevance
“…PPIs and H2RAs, which are acid-suppressant drugs, are commonly prescribed as chronic preventive and therapeutic drugs for the treatment of peptic ulcers and gastroesophageal reflux disease. However, studies have reported that chronic administration of PPIs decreases vitamin C levels in gastric juices through hyposecretion and the instability of ascorbic acid, which is related to hypochlorhydria induced by potent acid suppression (31)(32)(33). Furthermore, chronic H2RA or PPI use has been shown to be associated with the development of serum vitamin B12 deficiency through PPI-associated malabsorption due to decreased release of vitamin B12 from ingested food (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…PPIs and H2RAs, which are acid-suppressant drugs, are commonly prescribed as chronic preventive and therapeutic drugs for the treatment of peptic ulcers and gastroesophageal reflux disease. However, studies have reported that chronic administration of PPIs decreases vitamin C levels in gastric juices through hyposecretion and the instability of ascorbic acid, which is related to hypochlorhydria induced by potent acid suppression (31)(32)(33). Furthermore, chronic H2RA or PPI use has been shown to be associated with the development of serum vitamin B12 deficiency through PPI-associated malabsorption due to decreased release of vitamin B12 from ingested food (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, suggest that vitamin C supplements should be avoided in patients receiving proteasome inhibitor therapy. In particular, we recommend that patients who are under treatment with bortezomib should not take more than 500 mg of vitamin C. Specifically, it should be avoided at least 12 h before and after bortezomib treatment as the half-life of oral ascorbic acid in plasma is 10 h. 7,35 The transport and the accumulation of vitamin C depend on several mechanisms, including diet as well as modulating factors, such as proton pump inhibitors, 36 which increase gastric pH and reduce the stability and absorption of vitamin C; or dexamethasone, which induces sodium dependent vitamin C transporters and increases the accumulation of ascorbic acid, as shown in an osteoclastic cell model. 37 Importantly, our study shows that vitamin C supplementation decreases the efficacy of bortezomib treatment and outcome in vivo even at relatively low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of vitamin B12 are associated with both types of drugs, and proton-pump inhibitors reduce vitamin C levels. 16,17 It is likely that many more nutrients are affected. Indeed many different nutrients are needed for normal cognitive function.…”
Section: Act Notesmentioning
confidence: 99%